2010
DOI: 10.3899/jrheum.090835
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Prognostic Significance of Parotid Scintigraphy in 405 Patients with Primary Sjögren’s Syndrome

Abstract: Patients with SS presenting with severe scintigraphic involvement at diagnosis had a more pronounced autoimmune expression, a higher risk of developing systemic features and lymphoma, and a lower survival rate. Study of the degree of salivary gland dysfunction at diagnosis by parotid scintigraphy offers valuable clinical information on the prognosis and outcome of primary SS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 27 publications
2
31
0
2
Order By: Relevance
“…Patients with pSS having risk factors for progression to lymphoma should be closely monitored (persistent enlargement of parotid glands, splenomegaly, lymphadenopathy, purpura, leg ulcers, neutropenia, low levels of C4, and mixed cryoglobulinemia) [1,6]. CD4+ lymphocytopenia [2] and severe parotid scintigraphic involvement at diagnosis [7] seem to be useful clinical predictor in two recent studies. The identiWcation of predictive factors is not possible in our study in view of the low number of cases observed making a multivariate regression analysis not possible.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with pSS having risk factors for progression to lymphoma should be closely monitored (persistent enlargement of parotid glands, splenomegaly, lymphadenopathy, purpura, leg ulcers, neutropenia, low levels of C4, and mixed cryoglobulinemia) [1,6]. CD4+ lymphocytopenia [2] and severe parotid scintigraphic involvement at diagnosis [7] seem to be useful clinical predictor in two recent studies. The identiWcation of predictive factors is not possible in our study in view of the low number of cases observed making a multivariate regression analysis not possible.…”
Section: Discussionmentioning
confidence: 99%
“…11 Parotid scintigraphy has greater sensitivity (80%) and specificity (86%) 10 and evaluates the grade of involvement of the major salivary glands; severe involvement (grade IV) at diagnosis is prospectively associated with an increased risk of lymphoma and death. 21 Immunological study must include determination of autoantibodies to Ro/SS-A and La/SS-B antigens, which are positive in 50-70% of patients and are the only immunological parameter included in the current criteria, with a low sensitivity (33-46%) but a specificity of 100%. 10 Other parameters that should be tested for, or ruled out, are complement levels, serum monoclonal band, and cryoglobulins (hypocomplementaemia, monoclonal gammopathy, and mixed cryoglobulinaemia are associated with increased risk of lymphoma and death).…”
Section: Haematologicalmentioning
confidence: 99%
“…Nonetheless, few studies evaluated the centrality and dispersion of these quantitative scintigraphic indices in well-characterized groups of controls, and the validity and acceptance of such criteria still remain to be established. In which relates to SS, a recent report has shown a correlation between the severity of the scintigraphic involvement and a more pronounced autoimmune involvement with an increased risk to develop systemic features, lymphoma, and a lower survival rate [37]. Other reports also substantiate the relevance of scintigraphy in the assessment of glandular dysfunction and of the disease severity [38,39].…”
Section: Methodsmentioning
confidence: 96%